Plant Selection for Bioretention Systems and Stormwater Treatment Practices - Hunt, William F. (SpringerBriefs in Water Science and Technology, 2015)
Landscape/Regional and Urban Planning; Water Quality/Water Pollution; Hydrology/Water Resources; Urban Ecology